Diagnostic evaluation of the sacroiliac joints for axial spondyloarthritis: should MRI replace radiography?. Issue 11 (25th August 2022) - Poddubnyy, Denis; Diekhoff, Torsten; Baraliakos, Xenofon; Hermann, Kay Geert A; Sieper, Joachim
Abstract : The possibility of detection of structural damage on magnetic resonance imaging (MRI) of sacroiliac joints raises the question of whether MRI can substitute radiographs for diagnostic evaluation and to a further extent for classification of axial spondyloarthritis (axSpA). In this viewpoint, we will argue that it is time to replace conventional radiographs with MRI for the assessment of structural changes in sacroiliac joints. This message is based on current data on the following questions: (1) How reliable are conventional radiographs in the diagnosis of axSpA overall and radiographic axSpA in particular? (2) How does T1-weighted MRI compare to radiographs in the detection of sacroiliitis? (3) Are there now other (better) MRI sequences than T1-weighted, which might be more suitable for the detection of structural lesions? (4) Which MRI sequences should be performed for the diagnostic evaluation of the sacroiliac joints? (5) Do we have data to define sacroiliitis based on structural changes detected by MRI?